Immune potentiating role of protein, probiotic and symbiotic supplementation in moulted White Leghorn hens. (1st February 2015) - Anwar, H.; Rahman, Z.U.; Javed, I.; Muhammad, F.
This study investigated the effects of high protein, probiotic and symbiotic supplementation on the immunity of culled moulted White Leghorn hens. Cage-housed hens (n = 240) aged about 70 weeks were moulted by including zinc in the diet. The moulted hens were randomly divided in four treatment groups: control group (G1; CP 16% in basal diet), high protein group (G2; CP 18% in basal diet), probiotic supplemented group (G3; symbiotic at a dose rate of 85 mg L-1 in drinking water + CP 16% in basal diet), and symbiotic group (G4; probiotic at a dose rate of 85 mg L-1 in drinking water + CP 16% in basal diet). Ten birds from each group were euthanised at 5% peak (5P), full peak (FP), and end of production (EP). Blood samples were taken for serum to estimate geometric mean antibody titre (GMT) against Newcastle disease virus (NDV) and egg drop syndrome (EDS) virus. Macrophages were isolated from abdominal exudates (AE) to observe their engulfment response and their nitric oxide (NO) production. 2, 4-Dinitrochlorobenzene (DNCB) was inoculated on the skin of five birds in each group to evaluate the delayed type hypersensitivity response by determining the skin thickness. The overall humoral antibody GMT against NDV in the groups was higher in G2, G3 and G3 compared to G1. GMT value against EDS was higher in G2 compared to G1. A significant increase (P ≤ 0.01) in macrophage engulfment and NO production was seen in G2 and G4 compared to the G1. The DNCB inoculated skin thickness response remained higher (P ≤ 0.01) in G2 until FP than the other groups. A diet rich in protein or supplemented with a probiotic or a symbiotic enhances the body immunity of moulted hens.